Encyclopedia of Drug Metabolism and Interactions 2012
DOI: 10.1002/9780470921920.edm015
|View full text |Cite
|
Sign up to set email alerts
|

UDP‐Glucuronosyltransferases: Pharmacogenetics, Functional Characterization, and Clinical Relevance

Abstract: UDP‐glucuronosyltransferase (UGT)‐catalyzed conjugation reactions play an important role in the metabolism of both xenobiotics and endogenous compounds. The frequency of UGT involvement in xenobiotic drug metabolism has increased as the ability to design out other routes of metabolism (i.e., cytochrome P450) has improved. To this end, the primary goal of this chapter is to serve as a compendium for the significant amount of information surrounding UGTs that has been compiled to date. Where relevant, the chapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 461 publications
0
4
0
Order By: Relevance
“…Previous studies have reported a significant correlation between UGT1A6/UGT1A9 expression using HLM . Correlations between UGT 1A6, 1A9 and 2B7 protein content may be explained by common regulatory factors including PXR, CAR, HNF‐1α and HNF‐4α . Additionally, UGT1A9 and UGT2B7 terminate the biological activity of arachidonic acid metabolites and hence are integral to the regulation of renal haemodynamics .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported a significant correlation between UGT1A6/UGT1A9 expression using HLM . Correlations between UGT 1A6, 1A9 and 2B7 protein content may be explained by common regulatory factors including PXR, CAR, HNF‐1α and HNF‐4α . Additionally, UGT1A9 and UGT2B7 terminate the biological activity of arachidonic acid metabolites and hence are integral to the regulation of renal haemodynamics .…”
Section: Discussionmentioning
confidence: 98%
“…Drug-metabolizing enzymes responsible for the phase II conjugative pathways include the UDPglucuronosyltransferases (UGTs), sulfotransferases, N-acetyltransferases, glutathione transferases, methyltransferases, and acyl-CoA synthetases. Examples of phase I and phase II enzymes, along with their respective cofactors, substrates, inhibitors, and tissue location, are shown in Tables 1 and 2 (Riddle and Jencks, 1971;Trager, 1989;Ghersi-Egea et al, 1993;Matsui and Homma, 1994;Riley and Hanzlik, 1994;Dutton, 1997;Rendic and Di Carlo, 1997;Burchell et al, 1998;Halpert et al, 1998;Burchell, 1999;Weinshilboum et al, 1999;Tukey and Strassburg, 2000;Dalvie et al, 2002;Ortiz de Montellano and De Voss, 2002;Coughtrie and Fisher, 2003;Ding and Kaminsky, 2003;Nelson and Trager, 2003;Guengerich, 2005;Satoh and Hosokawa, 2006;Cashman, 2008;Dourado et al, 2008;Nakamura et al, 2008;Decker et al, 2009;Remmel and Zhou, 2009;Strolin Benedetti, 2011;Fasinu et al, 2012;Foti and Fisher, 2012;Garattini and Terao, 2012). A number of comprehensive resources detailing the chemistry and reaction mechanisms for many of the enzymes are readily available (Trager, 1989;Riley and Hanzlik, 1994;Burchell et al, 1998;Halpert et al, 1998;Burchell, 1999;Dalvie et al, 2002;…”
Section: Introductionmentioning
confidence: 99%
“…With numerous pharmaceuticals such as propofol, irinotecan/SN-38 and opioids as well as many important endogenous compounds such as bilirubin, hormones, and bile acids known to undergo glucuronidation, in vitro systems capable of carrying out glucuronidation reactions have received a significant amount of attention in recent years [25,26]. …”
Section: Discussionmentioning
confidence: 99%